Comparison of the Outcome of Conventional Osteosarcoma at Two Specialist International Orthopaedic Oncology Centres. (2004) - Ford, Samuel; Saithna, Adnan; Grimer, Robert J.; Picci, Piero
Abstract : Objective : To determine the prognostic value of patient and treatment parameters in osteosarcoma, and whether these are equally important across international boundaries. Design : Retrospective, cross-sectional study of 428 patients diagnosed with around-knee osteosarcoma, between 1990 and 1997 in Birmingham, UK, and Bologna, Italy. Disease-free survival (DFS) and overall survival (OS) assessed by Kaplan–Meier, Fisher's PLSD and Cox proportional hazard regression. Results : Five-year DFS and OS were 56 and 73% at Centre 1, compared to 43 and 60% at Centre 2 ( P =0.0022 and P = 0.025, respectively). The most important bad prognostic factors for DFS and OS respectively were raised alkaline phosphatase at diagnosis ( P =0.002 and P =0.003), tumour necrosis < 90% following chemotherapy ( P =0.001 and P = 0.004) and volume > 150cm 3 at diagnosis ( P =0.04 and P =0.006). The most significant combination of bad prognostic factors was alkaline phosphatase and tumour necrosis. A total of 73% of patients at Centre 1 had greater than 90% necrosis of the tumour following neoadjuvant chemotherapy compared with 29% at Centre 2. Conclusions : Tumour-based prognostic factors have similar significance across international boundaries. Chemotherapy effectiveness appears to be a major factor in explaining the survival difference between the two centres.